Debriefing in pediatrics - Su Jin Cho (Korean Pediatric Society, 2015)
Debriefing is a conversational session that revolves around the sharing and examining of information after a specific event has taken place. Debriefing may follow a simulated or actual experience and provides a forum for the learners to reflect on the experience and learn from their mistakes. Originating from the military and aviation industry, it is used on a daily basis to reflect and improve the performance in other high-risk industries. Expert debriefers may facilitate the reflection by asking open-ended questions to probe into the framework of the learners and apply lessons learned to future situations. Debriefing has been proven to improve clinical outcomes such as the return of spontaneous circulation after cardiac arrest and the teaching of teamwork and communication in pediatrics. Incorporating debriefing into clinical practice would facilitate the cultural change necessary to talk more openly about team performance and learn from near misses, errors, and successes that will improve not only clinical outcome but also patient safety.